Employee Turnover: Career Growth, Salary, Job Satisfaction, Organization Culture - Emmy Junianti (Dinasti International Journal of Management Science, 2023)
The purpose of the study is to prove whether there is an influence between career growth and employee turnover, second between salary and employee turnover, third between job satisfaction and employee turnover, and organizational culture with employee turnover, with a qualitative literature review. The research method used is qualitative using a literature review by searching scientific articles from several reputable international index journals and also national journals. The results showed that the three variables had their respective influences from the literature review of scientific articles obtained related to variables, besides that clearly there were also gaps in this study, namely transformational leadership, tenure, trust, compensation, employes retention, work environment, stress, Pay, Promotion Working Conditions Nature of the Work. The recommendation given by the researcher in this study is that for future research can be used variables that exist and are found with different research methods and research objects.